2020
DOI: 10.3390/ani10081437
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Infiltrating Lymphocytes in Pet Rabbit Mammary Carcinomas: A Study with Relevance to Comparative Pathology

Abstract: Tumor infiltrating lymphocytes (TILs) serve as prognostic biomarker in human breast cancer. Rabbits have the potential to act as animal model for human breast cancer, and close similarities exist between the rabbit and human immune system. The aim of this study is to characterize TILs in pet rabbit mammary carcinomas and to statistically correlate results with histological and immunohistochemical tumor characteristics. Microscopic evaluation of TILs was performed in hematoxylin and eosin stained sections of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Still, in cancer, the role of this multifaceted cellular population, which serve as nexus between innate and adaptive immunity, is still poorly understood and studies addressing this topic in both human and veterinary medicine are surprisingly few. Actually, most of the oncology studies and large study groups are focused on lymphocytes and on their role in cancer immune response (4)(5)(6)(7)(8)(9)(10). Macrophages are a wide-ranging population of immune cells characterized by broad heterogeneity, high plasticity, and remarkable ability to sense changes in the surrounding microenvironment and respond to it.…”
Section: Introductionmentioning
confidence: 99%
“…Still, in cancer, the role of this multifaceted cellular population, which serve as nexus between innate and adaptive immunity, is still poorly understood and studies addressing this topic in both human and veterinary medicine are surprisingly few. Actually, most of the oncology studies and large study groups are focused on lymphocytes and on their role in cancer immune response (4)(5)(6)(7)(8)(9)(10). Macrophages are a wide-ranging population of immune cells characterized by broad heterogeneity, high plasticity, and remarkable ability to sense changes in the surrounding microenvironment and respond to it.…”
Section: Introductionmentioning
confidence: 99%
“…Schöniger and coworkers found that mammary tumours in pet rabbits frequently have secretory activity, and most commonly are estrogen and progestogen receptor negative [ 21 , 22 ]. Immunological characterisation by the determination of tumour infiltrating lymphocytes and immunostaining for the immunosuppressive enzyme IDO1 uncovered that the majority of rabbit mammary tumours have low immunogenicity [ 23 ]. Schöniger suggested that pet rabbits may provide useful models to study secretory carcinomas, as well as low immunogenic triple-negative breast cancers.…”
Section: Meeting Reportmentioning
confidence: 99%